2006
DOI: 10.1073/pnas.0606256103
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of atmospherically relevant ions between bulk water and the water/vapor interface

Abstract: Recently, surface-sensitive spectroscopy data and molecular dynamics simulations have generated intense interest in the distribution of electrolyte ions between bulk water and the air͞water interface. A partitioning model for cations and anions developed for biopolymer surface is extended here to interpret the effects of selected acids, bases, and salts on the surface tension of water. Data for electrolytes were analyzed by using a lower-bound value for the number of water molecules in the surface region [0.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
230
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(248 citation statements)
references
References 32 publications
15
230
1
1
Order By: Relevance
“…As seen in Table 2, the trends observed for molecular hydrocarbon surface parallel those previously reported for ion partitioning at the air-water surface; 13,14 comparisons of ion distributions near these surfaces, obtained from molecular dynamics simulations, yield a similar conclusion. 36 Alkali metal cations are strongly excluded, GuH + is much less excluded than the other cations, and the rank order of partitioning of anions matches their placement in the traditional biopolymer Hofmeister series.…”
Section: Hydrocarbon Model Compoundssupporting
confidence: 83%
See 3 more Smart Citations
“…As seen in Table 2, the trends observed for molecular hydrocarbon surface parallel those previously reported for ion partitioning at the air-water surface; 13,14 comparisons of ion distributions near these surfaces, obtained from molecular dynamics simulations, yield a similar conclusion. 36 Alkali metal cations are strongly excluded, GuH + is much less excluded than the other cations, and the rank order of partitioning of anions matches their placement in the traditional biopolymer Hofmeister series.…”
Section: Hydrocarbon Model Compoundssupporting
confidence: 83%
“…1A. Also tabulated in Table 1 are the corresponding surface tension increments 13,14 and the intrinsic (composite) thermodynamic quantities b 1 (K p,3 -1) characterizing the net accumulation or exclusion of these salts for both molecular hydrocarbon and air-water surfaces (Eq. 1).…”
Section: Analysis Of Salt Effects On Model Compound Solubility Using mentioning
confidence: 99%
See 2 more Smart Citations
“…3) showed that while F À prefers to be fully solvated in the bulk, the other ions are increasingly present at the interface as one proceeds down the series, which has also been predicted in theoretical studies using a partitioning model. 98 Oxidants such as OH and O 3 are also predicted to be stable at the interface, [99][100][101] increasing the interface reactivity.…”
Section: Chemistry At the Interface Of Sea Salt Particlesmentioning
confidence: 99%